The Influence Of Organizational Climate, Leadership, And Motivation On Employee Performance Of PDAM Tirta Musi Palembang - M. Hafis Erlangga; Juhaini Alie; Tien Yustini (Syntax Corporation, 2022)
This study aims to determine the effects of organizational climate, leadership, and motivation on employee performance at PDAM Tirta Musi Palembang. The method used in this research is a descriptive quantitative method by multiple linear regression analysis tests. The sample in this study is the employees who are in the PDAM Tirta Musi Palembang. The results showed that the value of the calculated organizational climate variable T (4,540) > T table (1,969) means that there is an influence between the organizational climate of the employee performance, the value of the calculated leadership variable T (8,040) > T table (1,969) means that there is an influence between the leadership of the employee performance, the value of the calculated motivation variable T (9,999) > T table (1, that there is an influence of the organizational climate, leadership, and motivational variables on employee performance.